Epidemiology: Count the dead, measure the living - Whitlock, G.; Huxley, Rachel (2011)
Populations all around the world are becoming more obese, but some are doing so much faster than others. Yet even in seriously affected populations, blood pressure, cholesterol and coronary heart disease death rates continue to fall. Is obesity a trifling matter, or is it just less telling than everything else put together? © 2011 Macmillan Publishers Limited. All rights reserved.